Development of serious computer game based training module and its integration into working at heights mine site induction - Part I - Stothard, Phillip; van den Hengel, A. (AusIMM, 2010)
This paper reports the findings of a collaborative project that developed and demonstrated a serious computer game (SCG) based simulation training module for mine site inductions. It is the first of two papers. The project was collaboration between the University of New South Wales, the University of Adelaide, BHPB Olympic Dam Expansion, Resources and Engineering Skills Alliance, TAFESA and Skills DMC. The project was a pilot aimed at improving mine site inductions by developing a prototype SCG for trainers to incorporate into their regular training activities. The outcome was a high quality generic SCG that provides an interactive visualisation of an Australian mine site operation under construction. The conclusions and recommendations derived from this part of the study are summarised and discussion on the improvement of the SCG based simulation module is presented and some recommendations made. Scientific testing of the module and its site deployment are presented in the subsequent paper.